Occupational lung fibrosis, cancer of the larynx and pneumonia of repetition in an aged patient: an interdisciplinary case study - Rocha Oliveira, Débora; de Gouveia Pereira, Maria Alice; Silvia Frangella, Vera; Luque, Alexandre; de Souza, Andréa (O Mundo da Saúde, 2009)
Lung fibrosis may have a great number of systemic complications such as malnutrition and the reduction of functional capacity. Treatment must be individualized and designed for minimizing symptoms, optimizing functional condition and reducing health care expenses. This study aimed to evaluate the impact of an interdisciplinary approach to rehabilitating an aged patient with fibrosis and malnutrition. We did interdisciplinary case study of an octogenarian with occupational lung fibrosis, sequels from cancer of the larynx, megaesophagus, repetition pneumonia, energetic-proteic malnutrition, kinetic-functional diagnostic of functional capacity reduction and a high deficit of deglutition, with broncoaspiration. Multidisciplinary meetings were done aiming at establishing an adequate therapeutic option for improving the patient health condition. Adhesion was periodically monitored regarding nutritional behaviors, the development of specific maneuvers for deglutition and exercises programmed by the speech therapist and the physiotherapy. The direct and constant evaluation of clinical and nutritional evolution produced adjustments of behaviors prescribed by the interdisciplinary team. Due to interventions the patient presented a 3,2kg weigh gain, improvements of functional capacity and nutritional condition (a 21% gain of lean mass); a 100% increase in maximum voluntary contraction for the main muscular groups. The respiratory questionnaire also evidenced improvements in quality of life, with an impact in dyspnea control. The improvement of deglutition allowed a gradual reintroduction of reduced volumes of oral diet. We concluded that the constant association and evaluation of nutritional, phonoaudiologic therapies and endurance and force training were vital, showing the necessity and importance of an interdisciplinary approach in lung rehabilitation, especially in old people.